JARINGAN PERNIAGAAN HITU SEBAGAI BANDAR REMPAH DAN KAJIAN POTENSI PEMBELAJARAN SEJARAH DALAM KURIKULUM MERDEKA UNTUK JENJANG SMK - Ersanda, Privera Ajeng; Wahyudi, Deny Yudo (Universitas Negeri Malang, 2023)
Abstract: This study discusses the Hitu spice trade network and studies the potential for learning history in the Independent Curriculum for the SMK level. The writing of this study uses the literature study method by conducting an assessment of various literature in the form of articles, books, scientific journals, and previous studies that is relevant to the topic to be studied. The result of writing this study is that the Maluku Islands have been known as a trade network in the archipelago. The growth of the Hitu spice trading network is related to the creation of interaction and connectivity with local and foreign traders. Having a strategic location, Ambon Island is a place for boats and ships to stop as well as a spice trading market. This is because the Ambon coastal area connects ports or ports in the Maluku Islands which form a local network for trading activities with the main commodities being cloves and nutmeg. With the increasing number of Hitu, this led to the formation of a kingdom known as the Tanah Hitu Kingdom and was formed by the Four Primes. The arrival of the Portuguese to Hitu initially did not have a bad influence, but over time there were differences in interests which led to the Portuguese being expelled from Hitu. Then at the end of the 16th century the arrival of the Portuguese was followed by the Dutch and in 1605 succeeded in subduing the Portuguese and controlling Ambon. In an effort to achieve the learning objectives in the Independent Curriculum, vocational school history subject teachers are required to be able to design learning by utilizing various media and learning models that support the implementation of the Independent Curriculum, namely digital-based learning media and project-based learning models. Thus, the purpose of writing this study was to design an innovative and creative history lesson, and it is hoped that it will create future generations who are educated and able to compete globally in order to advance the quality of education in Indonesia. Abstrak: Kajian ini membahas mengenai jaringan perniagaan rempah Hitu dan kajian potensi pembelajaran sejarah dalam Kurikulum Merdeka untuk jenjang SMK. Penulisan kajian ini menggunakan metode studi pustaka dengan melakukan pengkajian terhadap berbagai literatur baik berupa artikel, buku, jurnal ilmiah, dan penelitian terdahulu yang relevan dengan topik yang akan dikaji. Hasil dari penulisan kajian ini adalah Kepulauan Maluku telah dikenal sebagai jaringan perniagaan di Nusantara. Tumbuhnya jaringan perniagaan rempah Hitu berkaitan dengan terciptanya interaksi dan konektivitas dengan para pedagang lokal dan asing. Memiliki letak yang strategis, Pulau Ambon menjadi tempat singgah perahu dan kapal sekaligus pasar perniagaan rempah. Hal tersebut karena wilayah pesisir Ambon menghubungkan pelabuhan atau bandar di Kepulauan Maluku yang membentuk jaringan lokal bagi aktivitas perniagaan dengan komoditi utama cengkeh dan pala. Dengan semakin ramainya Hitu, maka mendorong terbentuknya suatu kerajaan yang dikenal dengan Kerajaan Tanah Hitu dan dibentuk oleh Empat Perdana. Kedatangan Portugis ke Hitu pada awalnya tidak memunculkan pengaruh buruk, namun seiring berjalannya waktu terdapat perbedaan kepentingan yang membuat Portugis terusir dari Hitu. Kemudian pada akhir abad ke 16 kedatangan Portugis disusul oleh Belanda dan pada tahun 1605 berhasil menundukkan Portugis serta menguasai Ambon. Sebagai upaya mencapai tujuan pembelajaran dalam Kurikulum Merdeka, guru mata pelajaran sejarah SMK dituntut harus mampu mendesain pembelajaran dengan memanfaatkan berbagai media dan model pembelajaran yang menunjang penerapan Kurikulum Merdeka yakni media pembelajaran berbasis digital dan model pembelajaran berbasis projek. Sehingga, tujuan penulisan kajian ini dilakukan untuk mendesain pembelajaran sejarah yang inovatif dan kreatif, serta diharapkan dapat mewujudkan penerus bangsa yang terdidik dan mampu bersaing secara global guna memajukan kualitas pendidikan di Indonesia.